2002
DOI: 10.1038/sj.onc.1205646
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of MMP-9 in ERK-mutated stable transfectants inhibits glioma invasion in vitro

Abstract: We previously showed that enhanced expression of MMP-9, an endopeptidase that digests basementmembrane type IV collagen, is related to tumor progression in vitro and in vivo; antisense-MMP-9 stably transfected clones were less invasive than untransfected parental cells and did not form tumors in nude mice. In this study, we examined the role of ERK-1 in the regulation of MMP-9 production and the invasive behavior of the human glioblastoma cell line SNB19, in which ERK1 is constitutively activated. SNB19 cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
59
0
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(68 citation statements)
references
References 35 publications
(43 reference statements)
6
59
0
3
Order By: Relevance
“…Daoy cells were transfected with plasmid constructs containing ERK dominant negative mutant (Dn-ERK) (17), MMP-9 expressing cDNA (pcMMP-9) construct or commercial MMP-9 siRNA (25 and 50μl of 10mM). Briefly, plasmid containing either Dn-ERK or pcMMP-9 was mixed with fuGene HD reagent (1:3 ratio) in 500 μL of serum free medium and left for half and hour for complex formation.…”
Section: Transfection With Plasmidsmentioning
confidence: 99%
“…Daoy cells were transfected with plasmid constructs containing ERK dominant negative mutant (Dn-ERK) (17), MMP-9 expressing cDNA (pcMMP-9) construct or commercial MMP-9 siRNA (25 and 50μl of 10mM). Briefly, plasmid containing either Dn-ERK or pcMMP-9 was mixed with fuGene HD reagent (1:3 ratio) in 500 μL of serum free medium and left for half and hour for complex formation.…”
Section: Transfection With Plasmidsmentioning
confidence: 99%
“…These changes in cell physiology have been previously linked to the basal level of ERK activation (65,66). The extent of cell growth inhibition (nearly 100%) was unanticipated.…”
Section: Fig 4 Erk Activation By Csuparmentioning
confidence: 75%
“…Epidermal growth factor-and scatter factor/hepatocyte growth factor-induced MMP-9 expression in keratinocytes was mediated by ERK1/2 activation and could be inhibited by treatment with MEK inhibitor PD98059 (38). Moreover, transfection of constitutively active MEK increased MMP-9 expression in NIH3T3 cells, whereas catalytically inactive ERK1 blocked MMP-9 expression in glioblastoma cells (39). In contrast, in the current study a negative correlation was observed between p38 MAPK activity and calcium-induced MMP-9 gene expression in normal/premalignant oral keratinocytes.…”
Section: P38 Mapk Negatively Regulates Mmp-9 In Oral Cancermentioning
confidence: 90%